The K-popification of Anies Baswedan: Exploring fandom culture and youth involvement in Indonesia's 2024 election - Putri, Salsa Della Guitara; Purwaningsih, Titin (Universitas Muhammadiyah Ponorogo, 2026)
The 2024 Indonesian presidential election marked a significant shift in political engagement, particularly among young voters, who leveraged digital platforms and fandom culture to promote their preferred candidates. This study explores the K-popification of Anies Baswedan’s campaign, a phenomenon where youth-driven political participation mirrored K-pop fandom dynamics, transforming traditional electoral strategies. By utilizing Philip Niffenegger’s 4P Model of Political Marketing which involved Product, Promotion, Price, and Place, this research examines how Anies Baswedan's campaign evolved into a fan-centric movement that increased visibility, engagement, and voter mobilization. The study employs a qualitative case study approach, analyzing social media content, grassroots initiatives, and digital activism strategies that framed Anies Baswedan as an